Bioactive‐rich extracts of persimmon, but not nettle, Sideritis, dill or kale, increase eNOS activation and NO bioavailability and decrease endothelin‐1 secretion by human vascular endothelial cells. (5th July 2013) - Woodcock, Mark E; Hollands, Wendy J; Konic‐Ristic, Aleksandra; Glibetic, Maria; Boyko, Nadiya; Koçaoglu, Bike; Kroon, Paul A
Abstract BACKGROUND There is increasing evidence that consumption of plant bioactives such as polyphenols and glucosinolates reduces cardiovascular disease risk and improves endothelial function. In the Black Sea area, a number of plants are consumed alone and as ingredients in traditional foods, and dill, nettle, kale, Sideritis and persimmon were identified as bioactive‐rich traditional food plants. The present study investigated the effects of plant extracts on cellular markers of endothelial function (eNOS activation and expression and ET‐1 secretion). RESULTS Treatment of human umbilical vein endothelial cells with persimmon extract significantly increased Akt and eNOS phosphorylation and nitric oxide metabolites and significantly decreased secretion of ET‐1 to the media after 24 h compared with a vehicle control (all P < 0.01). None of the other plant extracts significantly altered any markers of endothelial function. CONCLUSION These findings suggest that persimmon fruit contains bioactives that can improve endothelial function via activation of eNOS and reduction in ET‐1 secretion, but that dill, kale, Sideritis and nettle do not. © 2013 Society of Chemical Industry